BRAFV600E/pTERT double mutated papillary thyroid cancers exhibit immune gene suppression - Sigarteu Chindris, Ana-Maria; Rivera, Michael; Ma, Yaohua; Nair, Asha; Liu, Yi; Wang, Xue; Necela, Brian M.; Kachergus, Jennifer M.; Casler, John D.; Brett, Christopher; Rivas Mejia, Ana M.; Bernet, Victor J.; et al. (Frontiers in Endocrinology, 2024)
Introduction: BRAFV600E mutation (BRAF mut ) is common in papillary thyroid cancer (PTC), and most patients have an excellent outcome. However, a TERT-promoter mutation (pTERT mut ) in the presence of BRAF mut (BRAF mut pTERT mut ) has been demonstrated to confer a more aggressive behavior to PTC. Lymphocytic infiltration is often present in PTC. In this study, we sought to decipher the relationship between the BRAF and TERT mutations and immune gene dysregulation in tumor samples from a cohort of 147 samples of PTC.The abundance of 770 immune gene transcripts was determined by multiprex capture/detection and digital counting of mRNA transcripts using the NanoString nCounter® PanCancer Immune Profiling Panel.We identified 40 immune transcripts differentially expressed in BRAF mut pTERT mut vs BRAF mut pTERT wildtype (pTERT wt ) (P<0.05). Transcripts induced by BRAF mut alone were significantly repressed in BRAF mut pTERT mut samples, such as genes expressed by lymphoid cells, antigen-presenting cells, and cytotoxic cells, including chemokines, cytokines, checkpoint control proteins, interferon downstream markers, TNF superfamily proteins and BMP markers. A validation analysis using 444 samples from The Cancer Genome Atlas (TCGA) PTC dataset yielded similar results. Deconvolution analysis confirmed differences in the immune cell populations such as increased presence of M2 macrophages in the BRAF mut TERT mut Mayo cohort and a lower abundance of M1 macrophages in the BRAF mut TERT mut TCGA cohort compared to BRAF mut pTERT wt . Most of the immune gene pathways were enriched in the BRAF mut pTERT wt tumors in both Mayo and TCGA cohorts but not in BRAF mut TERT mut . BRAF mut pTERT wt had higher stromal lymphocytes infiltration as compared to BRAF wt pTERT wt tumors, corroborating the transcriptomic findings.4 Discussion: To our knowledge this is the first report of a potential link between TERT and the immune microenvironment, offering a explanation for the aggressive nature of BRAF mut pTERT mut PTC.